Agricultural practices influence foliar endophytic communities in coffee plants of different varieties - Humberto Castillo‐González; Joshua Bloomberg; Eduardo Alvarado‐Picado; Stephanie Yarwood; Priscila Chaverri (Agrosystems, Geosciences & Environment, 2024)
Abstract Fungal endophytes are pivotal components of a plant's microbiome, profoundly impacting its health and fitness. Yet, myriad questions remain concerning the intricate interactions between these microorganisms and their hosts, particularly in the context of agriculturally important plants such as Coffea arabica. To bridge this knowledge gap and provide a comprehensive framework, this study investigated how farming practices shape the taxonomic and functional diversity of phylloplane endophytes in coffee. Coffee plant leaves from two distinct producing regions in Costa Rica were sampled, ensuring the representation of various coffee varieties (Obatá, Catuaí, and Caturra), agricultural management methods (organic vs. conventional), sun exposure regimes (full sunlight/monoculture vs. natural shade/agroforestry), and leaf developmental stages (newly emerged asymptomatic vs. mature leaves). Fungal communities were characterized by employing both culture‐dependent and independent techniques (internal transcribed spacer 2 nuclear ribosomal DNA metabarcoding). The results showed a greater diversity of endophytes in mature leaves and conventionally managed plants, with coffee variety exerting an unclear influence. The effect of sun exposure was surprisingly negligible. However, data emphasize the benefits of agroforestry and organic farming, which are linked to reduced putative pathogens and heightened levels of potentially mutualistic fungi, fostering functionally diverse communities. Despite the role that plant microbiomes might play in agricultural production, the knowledge to shape endophytic communities through breeding or management is lacking. The results from this study provide a framework to understand how both plant and agricultural practices influence endophyte diversity within coffee crops. These insights hold promise for guiding future efforts to manipulate coffee microbial communities effectively.